IMPLEMENTASI TEKNOLOGI DALAM PENGEMBANGAN MAKANAN RINGAN KARAK KALIANG KHAS KOTA SOLOK - Eka Candra Lina; Caesar Welya Refdi; Prima Fithri; Wenny Surya Murtius (LPPM Universitas Andalas, 2020)
The business incubator has a role as a companion institution that helps entrepreneurs become independent. Incubator programs are presented in training, coaching, mentoring, and evaluating to reduce the risk of business failure, gaining market access, access to technology implementation, and other supporting access. The incubation activity for superior regional products is a collaboration between the Technology Business Incubator Unit under the Andalas University Science Techno Park (STP) with the City of Solok, aiming to create independent entrepreneurs who become the forerunners of industrial clusters. Small and Medium Enterprises (UKM) snacks are one type of business that focuses on development. Activities carried out in this incubation program are carried out in one-day seminars, technology implementation workshops, business mentoring / incubation, industrial visits, branding, and packaging. Solok typical snacks include processed cassava called karak kaliang and various chips from various raw materials, including pare chips. karak kaliang from Solok City has characteristics that other regions that produce the same food don't have. Karak Kaliang from Solok City is pure white in color, smaller in size than Karak Kaliang from other areas. There are several problems with snacks production, such as Cost production, product quality, high labor wages, the market consumer. After receiving a touch of innovation, Karak kaliang characters are produced in a more hygienic, healthier, and up-to-date manner with new packaging and branding, as well as the bitter melon chips. This program is expected to increase the typical snack market segment of Solok city, expand marketing, increase shelf-life, and product competitiveness. SME partners expected to become a pioneer for the advancement of the snack industry in Solok .